Insilico analysis on the complex relationship among antibiotic resistance, virulence genes and insertion sequences in Pseudomonas aeruginosa: DOI: 10.48129/kjs.14591 - K, Santhiya (Kuwait Journal of Science, 2022)
Pseudomonas aeruginosa is the most frequent nosocomial pathogen, causing many infections in people and posing significant health risks worldwide. The current work attempts to understand the connection between antibiotic resistance genes (ARG), virulence factors (VF), and insertion sequences (IS) in P. aeruginosa. Fifty-six P. aeruginosa complete plasmids were retrieved from the NCBI database for this investigation. The CARD and Resfinder tools are used to discover ARG in P. aeruginosa. The VF analyzer and ISsaga tools are used to identify virulence genes and insertion sequences in the sorted plasmids. Using the tool PHASTER, the participation of prophage and integrase genes was discovered. Resistance to sulfonamide and beta-lactam was the most common ARG among the plasmids. Fil, pil, and XCP secretion systems are prevalent virulence genes. The prophage, integrase, and transposons were also identified. The correlation analysis of ARG, VF, and IS revealed that ISs, rather than virulence factors, had the most significant effect on the P. aeruginosa genome studied. As a result, an understanding of infectious bacterial profiles regarding pathogenicity islands and mobile elements is required to gain knowledge of their distribution and limit their spread throughout the world.